Maintenance management of intelligent building (a case study of Perbadanan Putrajaya building) / Shahrul Azim Rambli - Rambli, Shahrul Azim (Faculty of Architecture, Planning and Surveying, 2010)
The intelligent building is one of a technology that consist of a system that can work or operate automatically without using the manual operation, the system will operate according to the schedule that has been set up by the building owner. The maintenance management of the intelligent building is different with the other conventional building, because to maintain the intelligent building must be whom that participate specialist on the system. The main factor was makes these buildings were call of intelligent building was on the aspect of technology usage, for example on the system. The system been adapted on this building were name by Building Control System BCS, this system are not authorized by the local industry but come from outsider country which is United State. On the aspect of maintenance of the intelligent building, it must be taken seriously, because with the careless of maintain it; it will gave the negative impact towards the building especially to the building system. This building was operate and been control by the BCS system, it consist 90% of the building system in the building such as lighting system, air conditioning system, lift system, pump, security and etc are control by the system.